Semen evaluation of Boer breeder bucks as influenced by lysine supplementation. - Balbin, A. J. M. (International Journal of Agricultural Technology, 2025)
Artificial insemination (AI) is widely used biotechnology tool applied to improve reproduction and genetics in livestock. The viability of the sperm cells is the most important factor to ensure successful insemination which can be achieved through proper nutrition management. The effect of amino acid supplementation, particularly additional of lysine in the diet of breeder bucks is studied. The production performance and quality of sperm cells produced by semen donors without supplementation (T1) is differentiated with donors receiving 1.75% lysine or low rate (T2), 2.45% or moderate rate (T3), and 3.15% or high rate of supplementation (T4) within two periods: Period 1 (Days 1-21) and Period 2 (Days 22 and onwards). The results showed that with lysine supplementation regardless of rate, animals are heavier than the animals that were not supplemented (p<0.05). Lysine supplementation positively affected on animal’s libido in terms of period consumed and the number of mountings before a successful ejaculation (p<0.05). The volume of semen increased (p<0.001); while sperm cell concentration, motility, fast progressive, slow progressive, circle and local motility rates were not significantly affected; however, positive effect on rate of immotile (p<0.01) and velocity (p<0.05) was observed. Considering all parameters, Treatment 2 lysine supplementation resulted to improve animal production and higher viability of sperm cells in both fresh and frozen-thawed state. Thus, 1.75% of lysine is recommended for inclusion to daily dietary concentrate ration.